Wajah Penerbitan Islam di Indonesia Radikal - Khamami Zada (JURNAL INDO-ISLAMIKA, 2011)
This paper discusses the radical façade of Islam demonstrated in number of media including articles, books and others in Indonesia. How Islam teaches to protect and apply its doctrines understood by some Indonesian Muslim activists and scholars representing some organizations is presented in this paper. It observes the continuity of the attempt of spreading quite radical Islamic doctrines by some publishers in the period of colonialization and that of independence. It argues that such the attempt has been influenced by the social and political changes, and led to actualize jihad notion as glorified by a number of Muslim countries in the words